Plants as antiparasitic agents: a review regarding portuguese ethnobotany - Sousa, Mariana; Cruz, Agostinho (Proceedings of Research and Practice in Allied and Environmental Health, 2023)
Background: Ethnobotany focuses on the communal use of plants, within this field, ethnobotanical studies play a crucial role identifying plants with potential therapeutic effects, preserving traditional knowledge and ancestral practices [1,2,3]. These studies allow the development of alternative therapies, which are crucial to support modern medicine [4]. Thus, the identification of plants with antiparasitic properties is vital for the development of new therapeutic options [5]. Plants such as Allium sativum and Mentha spicata have a history of use and serve as examples recognized for their antiparasitic properties [6]. Objective: The objective of this study is to identify ethnobotanical studies conducted in Portugal, with the aim of creating a list of plants that have been documented to have antiparasitic properties. Methods: A literature review was undertaken using PubMed, ScienceDirect, RCAAP and Web of Science, with the search equation (“Ethnobotanical studies” AND “Portugal”). Eligible studies were required to meet the criteria of being authentic ethnobotanical studies conducted in Portugal, that were digitally accessible and contain the list of plants along with their scientific names and documented purposes. The extracted information was summarized in tables. Results: A total of 56 species with documented antiparasitic uses were identified within the community. These species were utilized for addressing both ectoparasites and endoparasites, serving purposes in human and veterinary applications. The most cited plants included Mentha spicata and Mentha piperita. Remarkably, the Autonomous Region of Madeira had the highest number of identified antiparasitic plant species, totaling 22 species. Conclusions: This study successfully compiled a list of plants with antiparasitic properties within the community. The findings provide foundation for future research, including in vitro and in vivo studies, to validate and explore the efficacy of these plants as antiparasitic agents, and contribute to the development of alternative therapeutic options for managing parasitosis.